REQUIREMENTS FOR DIAGNOSTIC TOOLS OF COMPUTER SYSTEMS - Khoroshko, Volodymyr; Kuzavkov, Vasyl; Iankovskii, Oleg; Bolotiuk, Yuliia (Ukrainian Scientific Journal of Information Security, 2023)
The substantiation of the requirements for reliability, controllability and maintainability, as well as the determination of the probabilities of errors of the first and second kind during the operation of complex diagnostic tools for systems with built-in software is one of the main tasks that arise at the preliminary stage of development and design of this type of diagnostic tools. The readiness of the object of diagnostics can be characterized by the indicator of readiness - the probability of maintaining the operational efficiency of the object at an arbitrary moment in time when it is used for its intended purpose. This is especially important for complex technical information protection systems at facilities, which consist of many subsystems of various purposes and complexity. The formalized procedure proposed in the paper allows formulating requirements for complex diagnostic tools for computer systems and systems with built-in software in the absence of information about the importance of indicators characterizing the safety of the object at the previous stage of designing technical equipment, and substantiating them in the presence of a minimum amount of information on at the design stage of the latter.